Toward an understanding of the development of ownership feelings - Brown, Graham; Pierce, J.; Crossley, C. (2014)
Psychological ownership is increasingly recognized as a core feeling in the experience of work. Within jobs and the work context, there is a wide range of opportunities to experience psychological ownership. Yet empirical work on how feelings of ownership develop is lacking, and thus ways to develop psychological ownership in the workplace are not well understood. We explore the routes traveled to feelings of ownership by using job complexity as one example of work environment structure that affects the formation of psychological ownership. In two studies, we develop measures of the routes and confirm that perceived differences in one's work meaningfully predict psychological ownership. Collectively, the two studies provide insight into and offer suggestions for how ownership develops and ways in which managers might foster employee feelings of ownership toward their work. © 2013 John Wiley & Sons, Ltd.